Fetal alcohol spectrum disorders: an overview of current evidence and activities in the UK. Issue 7 (13th January 2021) - Schölin, Lisa; Mukherjee, Raja A S; Aiton, Neil; Blackburn, Carolyn; Brown, Sarah; Flemming, Kate M; Gard, Paul R; Howlett, Helen; Plant, Moira; Price, Alan D; Shields, Jennifer; Smith, Lesley A; et al.
Abstract : Estimates for the UK suggest that alcohol consumption during pregnancy and prevalence of fetal alcohol spectrum disorder (FASD)—the most common neurodevelopmental condition—are high. Considering the significant health and social impacts of FASD, there is a public health imperative to prioritise prevention, interventions and support. In this article, we outline the current state of play regarding FASD knowledge and research in the UK, which is characterised by a lack of evidence, a lack of dedicated funding and services, and consequently little policy formulation and strategic direction. We highlight progress made to date, as well as current knowledge and service gaps to propose a way forward for UK research.